2022
DOI: 10.3389/fcvm.2022.933060
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Cardiac Regeneration

Abstract: The mortality due to heart diseases remains highest in the world every year, with ischemic cardiomyopathy being the prime cause. The irreversible loss of cardiomyocytes following myocardial injury leads to compromised contractility of the remaining myocardium, adverse cardiac remodeling, and ultimately heart failure. The hearts of adult mammals can hardly regenerate after cardiac injury since adult cardiomyocytes exit the cell cycle. Nonetheless, the hearts of early neonatal mammals possess a stronger capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Previous studies found that the transition from glycolysis to fatty acid metabolism in postnatal hearts is consistent with the loss of cardiac regenerative capacity. 25 , 26 Furthermore, the activation of PKM2 was found to promote the G6PD‐dependent pentose phosphate pathway and stimulate cardiomyocyte proliferation after MI. 27 Because PKM2 and G6PD were not activated in the I/R+hydrogel group, the mechanism experiments were mainly conducted in the I/R+hydrogel group and I/R+rhCHK1‐hydrogel group, and relevant data were analyzed in these 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that the transition from glycolysis to fatty acid metabolism in postnatal hearts is consistent with the loss of cardiac regenerative capacity. 25 , 26 Furthermore, the activation of PKM2 was found to promote the G6PD‐dependent pentose phosphate pathway and stimulate cardiomyocyte proliferation after MI. 27 Because PKM2 and G6PD were not activated in the I/R+hydrogel group, the mechanism experiments were mainly conducted in the I/R+hydrogel group and I/R+rhCHK1‐hydrogel group, and relevant data were analyzed in these 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Developmental change and injury response of the heart lead to a metabolic shift to glycolysis for energy production [ 28 ]. Cancer cells have a higher capacity of proliferation and there exists a Warburg effect.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) remains a major cause of morbidity and mortality all over the world, causing approximately 17.9 million deaths per year in the United States [ 1 ]. Heart failure, the inability of heart to provide sufficient blood flow to the body, is largely attributed to the non-regenerative cardiomyocytes that provide contractility to the heart [ 2 ]. Myocardial injury results in cardiac remodeling and adverse fibrosis, resulting in fibrotic scar tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%